2011
DOI: 10.1007/s00299-011-1105-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of HD2 genes in seed germination and early seedling growth in Arabidopsis

Abstract: The Arabidopsis HD2 family of histone deacetylases consist of 4 members (HD2A, HD2B, HD2C, HD2D) that play diverse roles in plant development and physiology through chromatin remodelling. Here, we show that the transcripts of HD2 family members selectively accumulate in response to glucose through a HXK1-independent signal transduction pathway during the early stages of seedling growth. Germination was enhanced in hd2a null mutants relative to wild-type seeds. In contrast, hd2c mutants were restrained in germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 54 publications
3
46
0
Order By: Relevance
“…In conclusion, APO and AMPO can inhibit different aspects of plant growth at concentrations comparable to the effective concentration of commercial herbicides. The root growth defects were comparable to those seen in plants lacking function of HDA6 and HDA19 (RPD3/HDA1 superfamily; Supplemental Figure 9) and of HDT1 and HDT3 (plant-specific HD2 family) (Colville et al, 2011), supporting the hypothesis that this class of allelochemicals affects the germination and development of surrounding competitors by inhibiting one or several HDACs.…”
Section: Similar Phytotoxicity Of Hdac Inhibitors and Conventional Hesupporting
confidence: 54%
See 1 more Smart Citation
“…In conclusion, APO and AMPO can inhibit different aspects of plant growth at concentrations comparable to the effective concentration of commercial herbicides. The root growth defects were comparable to those seen in plants lacking function of HDA6 and HDA19 (RPD3/HDA1 superfamily; Supplemental Figure 9) and of HDT1 and HDT3 (plant-specific HD2 family) (Colville et al, 2011), supporting the hypothesis that this class of allelochemicals affects the germination and development of surrounding competitors by inhibiting one or several HDACs.…”
Section: Similar Phytotoxicity Of Hdac Inhibitors and Conventional Hesupporting
confidence: 54%
“…Of note, the plant-derived aminophenoxazinone APO showed the clearest correlation between effects on H3ac and gene expression in Arabidopsis, in agreement with APO effects being physiologically most relevant. Characterized mutants in single HDAC genes show less severe slowdown of root growth than plants treated with high concentrations of APO (Supplemental Figure 9; Colville et al, 2011), which suggests that the allelochemical either acts on other HDACs or that it inhibits more than one HDAC. Elucidating the specificity of the allelochemicals APO and AMPO in inhibiting different plant HDACs, and the consequences for different histones and for modifications at different histone residues, should therefore allow a better understanding of their direct chromatin targets.…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation has been demonstrated to function in different plant hormones (23,(26)(27)(28)(29), and several histone deacetylases are known to be involved in the regulation of gene expression (30)(31)(32)(33)(34)(35)(36)(37). The data presented here showed that the C-terminal domain of EIN2 (EIN2-C) is the key factor that drives alterations in histone acetylation during the ethylene response.…”
Section: Discussionmentioning
confidence: 64%
“…They found that AtHD2A prevents germination while AtHD2C enhances germination in the presence of Glc. In contrast to AtHD2A and AtHD2C, AtHDA7 is not induced by Glc (Colville et al, 2011), thereby making it unlikely that sugar sensing is involved in the seed germination defects observed in Athda7-2. The similarity between the Athda7-2 phenotype and TSA treatment (Tanaka et al, 2008) suggests a role for AtHDA7 in Arabidopsis seed germination.…”
Section: Discussionmentioning
confidence: 97%